A Review on Sugarcane Bagasse (SCB) based Composite Material - Loh, Y.R.; Rahman, Ekhlasur; Sujan, Debnath (School of Engineering & Science, Curtin University Sarawak Campus, 2012)
The natural and biodegradable features that delineated by the sugarcane bagasse (SCB) wastes have been attracting the attention of materials science researchers as a potential ingredient in composite materials. Eco-friendly considerations and anticipations have set the momentum for researchers to identify eco-friendly green materials with low pollutant indexes. A review of literature reveals that extensive research have been conducted in an attempt to reveal and further explore all plausible potentials of SCB. Manifold parts of the SCB can be utilised for the manufacturing of desirable composite materials that portray different levels of prominent properties and enhance magnificent performances. Researches on the impacts, performances and applications of the SCB in its original and unmodified condition have been duly considered and investigated. Transforming SCB into various forms by having it undergoes appropriate processes; and treating it with chemicals for properties modifications have been examined as well. This paper hence aims to review current literature concerning the utilisation and potentials of SCB waste for composite materials.